التخطيط السياحي وتكنولوجيا المعلومات والاتصال ودورهما في تنمية النشاط السياحي المعاصر - احداد موراد; شعبان كريمة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
يعد كل من التخطيط السياحي وتكنولوجيا المعلومات والاتصال من أهم الآليات الأساسية التي تساهم بشكل كبير في تنمية وإدارة النشاط السياحي المعاصر، فالأول يساعد على تحديد وصيانة الموارد السياحية والاستفادة منها بشكل رشيد وممنهج في الوقت الحاضر والمستقبل في إطار سياحة مستدامة، والثاني تتجلى أهميته في الخدمات التي توفرها مختلف التطبيقات الالكترونية في مجال التسويق السياحي الحديث. الكلمات المفتاحية: التخطيط السياحي؛ التنمية السياحية؛ تكنولوجيا المعلومات والاتصال؛ التسويق السياحي؛ التطبيقات الالكترونية. Abstract: Tourism planning, information and communication technology are among the most important basic mechanisms which contribute greatly to the development and management of contemporary tourism activity. The first helps in identifying and maintaining tourism resources and using them in a rational and systematic way, at the present and in the future in the context of sustainable tourism. And the second that is important present in the services provided by various electronic applications in the field of modern tourism marketing. Keywords: Tourism Planning; Tourism Development; Information and Communication Technology; Electronic Application; Tourist Marketing.